Indonesian as a Communication Tool in Accounting in the Digital Era - Iaia, Seven Rius; Jeremy, Gabriel Satrio; Siagian, Muhammad Arif; Akbar, Muhammad Rizki; Sinaga, Randa Yosua; Wulandari, Ayu Nadira (Yayasan Salam Cerdas Al-Fattah, 2024)
This paper aims to discuss the vital role of Indonesian as a communication tool in accounting, especially in facing challenges and opportunities in the digital era. This study uses library research that relies on primary and secondary data, taken from journals, books, websites, and other relevant sources. By strengthening the understanding of accounting terms and technologies that continue to develop through the use of clear and easy-to-understand language, accountants can improve their ability to adapt and keep up with the times. The importance of accounting training and mastery of foreign terms that are often used in accounting language is also highlighted. Therefore, Indonesian needs to be used to translate and explain these concepts into a more local and easier-to-understand context. Efforts to facilitate the use of Indonesian in accounting practice must be a primary concern so that all accountants can develop professionally and contribute optimally in an increasingly competitive business world